Petrogenesis of an early Cretaceous potassic lamprophyre dyke from Rongjeng, East Garo Hills, Shillong plateau, north-eastern India - Srivastava, Rajesh K.; Melluso, Leone; Sinha, Anup K. (My University, 2016)
An early Cretaceous potassic lamprophyre dyke, exposed near Rongjeng, East Garo Hills, Shillong plateau, north-eastern India, is a highly porphyritic rock with large phenocrysts of clinopyroxene, phlogopite, amphibole and olivine. Reversely zoned phlogopite and clinopyroxene grains indicate that some degree of interaction between magma batches of variable composition took place somewhere during the crystallization of the lamprophyre. Mineral composi-tions indicate its derivation from an alkaline magma comparable with those that filled the nearby Jasra potassic intrusion. Moreover, the geochemistry of the Rongjeng lamprophyre is distinctly different from that of the Damodar Valley lamproites, the Sung Val-ley carbonatitic-ijolitic intrusion, and the Antarctic ultramafic lamprophyres. The contrasting geochemi-cal affinity is suggestive of heterogenous lithospheric mantle sources, rather than input of plume-related magmatism.
Keywords: Geochemistry; Peterogensis; Lithospheric alkaline magmatism; Mantle heterogeneity; Potassic lamprophyre